Mindfulness-based cognitive therapy for psycho-oncology patients: an exploratory study. (7th January 2015) - Kingston, T.; Collier, S.; Hevey, D.; McCormick, M. M.; Besani, C.; Cooney, J.; O'Dwyer, A. M.
Abstract : Objectives: Mindfulness-based cognitive therapy (MBCT) is a group-based intervention similar to mindfulness-based stress reduction, but which includes cognitive therapy techniques. This study investigates its usefulness in the treatment of depressive, anxiety and stress/distress symptoms in cancer patients referred to a psycho-oncology service. It also examines whether effect on depression is mediated by self-compassion. Method: In phase 1 of this study, 16 cancer patients with mild/moderate psychological distress were randomised to MBCT ( n =8) or treatment as usual (TAU; n =8), and assessed pre- and post-treatment. Analysis of variance was performed to examine the effect of treatment on anxiety and depression. In phase 2, the TAU group received the intervention, and results of pre- and post-MBCT assessments were combined with those receiving MBCT in phase 1. Finally, both groups were followed up at 3 months. Results: In phase 1, the MBCT group had a significant improvement in mindfulness and a decrease in anxiety. Statistically significant improvements in both depression and anxiety were found at 3 month follow-up. Self-compassion appeared to mediate the effect on anxiety/depression. Conclusion: This small pilot study suggests that MBCT may have a beneficial effect on psychological variables often adversely affected in cancer in a heterogeneous cancer population.